2014
DOI: 10.1371/journal.pone.0090947
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Copy Number Variants on miRNA Genes in Autism by Monte Carlo Simulation

Abstract: Autism Spectrum Disorders (ASDs) are childhood neurodevelopmental disorders with complex genetic origins. Previous studies have investigated the role of de novo Copy Number Variants (CNVs) and microRNAs as important but distinct etiological factors in ASD. We developed a novel computational procedure to assess the potential pathogenic role of microRNA genes overlapping de novo CNVs in ASD patients. Here we show that for chromosomes # 1, 2 and 22 the actual number of miRNA loci affected by de novo CNVs in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…Autistic traits also have been associated with miR-211 deletions and duplications at miRNA Dysregulation in Psychiatry (66). Finally, two groups of investigators used CNV database searches and reported a large number of miRNAs, including miR-211, that overlap with known autism-associated CNVs (67,68). Again, miR-132 has been associated with autism disorders several times, suggesting it could be a particularly important miRNA (Supplement 1).…”
Section: Asdsmentioning
confidence: 99%
“…Autistic traits also have been associated with miR-211 deletions and duplications at miRNA Dysregulation in Psychiatry (66). Finally, two groups of investigators used CNV database searches and reported a large number of miRNAs, including miR-211, that overlap with known autism-associated CNVs (67,68). Again, miR-132 has been associated with autism disorders several times, suggesting it could be a particularly important miRNA (Supplement 1).…”
Section: Asdsmentioning
confidence: 99%
“…and Vaishnavi et al . reported that copy number variants or single nucleotide polymorphisms in miRNAs were correlated with ASD67. Nguyen et al .…”
mentioning
confidence: 99%
“…Another neurodevelopmental disorder associated with epigenetic dysregulation related to paternal chromosomal mutations is Rett syndrome caused by MECP2 on the X-chromosome. 9 Such data support a background genetic landscape influencing epigenetic processes, but given the relative fluidity of these processes, the role of environmental factors and how these might impact on neurodevelopment also needs to be considered. Moreover, MECP2 preferentially binds at cytosine-phosphate-guanine sites and silences downstream-regulated genes, but mutated forms are far less effective; they appear to be specifically involved with a neuron-related set of genes and interact with DNA methylation.…”
Section: Epigenetics and Neurodevelopmental Disordersmentioning
confidence: 99%
“…Furthermore, microRNAs are affected more than would be expected in copy-number variation-associated autism spectrum disorder. 9 Such data support a background genetic landscape influencing epigenetic processes, but given the relative fluidity of these processes, the role of environmental factors and how these might impact on neurodevelopment also needs to be considered. In a rat model of cocaine exposure, drug na€ ıve male rats of cocaine-exposed sires have memory formation deficits associated with reduced hippocampal N-methyl-D-aspartate-receptor synaptic plasticity.…”
Section: Epigenetics and Neurodevelopmental Disordersmentioning
confidence: 99%